Translation Analysis of Emotional Intelligence Term of Root Word on Working with Emotional Intelligence by Daniel Goleman - Hasyim, Nur; Nababan, M.R.; Djatmika,; Wiratno, Tri (International Journal of Psychosocial Rehabilitation, 2020)
The research focuses on translation technique and translation quality of root word on emotional intelligence terms in the book entitled Working with Emotional Intelligence by Goleman. The research goals are to a) describe the word class that was used to reveal emotional intelligence terms; b) describe the translation technique which was used in translating the emotional intelligence terms; c) describe the translation technique which influences the translation quality. The research is the descriptive qualitative paradigm by using a purposive sampling technique. There were three classes of words found in the source text. They were nominal, verbal, and adjectival. There are five categories of emotional intelligence. The frameworks of the categories are self-awareness, self-management, motivation, emphatic, and social ability. There were ten translation techniques in translating the emotional intelligence terms in each classification. There were established equivalence, transposition, pure borrowing, modulation, discursive creation, generalization, addition, deletion, implicitation, and literal translation. The quality translation score was 2.96 for nominal; 2.94 for verbal; and 2.90 for adjectival. From the translation versions, it could be concluded that the translation quality was excellent. It caused by choosing certain techniques that be able to keep translation quality stays high such as established equivalence, transposition, and modulation. Then, certain techniques were lowering the translation quality, such as deletion, addition, discursive creation, and literal translation.